The Security Perceptions of Armenia's Ruling Elite and Their Influence on Armenian-Russian Relations in 2008-2018 - Sukiasyan, Narek (YSU Journal of International Affairs, 2021)
The article explores the security perceptions of Armenia’s ruling political elite from the 2008 Russian-Georgian war to the post-April war period up to 2018 by applying constructivist methodology and the concept of security identity. The research relies on the speeches, interviews of the ruling elite, Government programs and relevant documents, and preelection programs of the ruling Republic Party of Armenia that reveal their perceptions of the structural factors (domestic-structural, regional-security, global-systemic) affecting the Russian direction of Armenia’s foreign policy. The article reveals that initially, the elite regarded the normalization of the relations with the neighbours as a way of overcoming domestic-structural vulnerabilities. The failure of the efforts in that direction resulted in the growth of the importance of the EU as means of modernization and regional stability. As this direction too did not meet the expectations, the belief of Russia’s indispensable role was reinstated in the eyes of the ruling elite. While it was expected that Armenia’s membership in Eurasian Economic Union would boost Armenia’s security under Russia’s regional security umbrella, the intensification of Russia’s arms sales to Azerbaijan had been creating discontent among the ruling elite which onlybecame more apparent after the 2016 “April war”.
Keywords: Foreign policy of the Republic of Armenia; Armenian-Russian relations; constructivism; security identity; discourse analyses; ruling elite of the Republic of Armenia